Ks. Andrzej Uciecha, Polemika św. Efrema z manicheizmem w „Refutationes”, Studia Antiquitatis Christianae. Series Nova 8, Katowice 2009, Księgarnia św. Jacka, ss. 240. - Żelazny, Jan (Vox Patrum, 2009)
nie dotyczy